Model Pembelajaran Problem Based Learning dengan Pendekatan Culturally Responsive Teaching untuk Meningkatkan Hasil Belajar Peserta Didik - Rochaminah, Sutji; Baid, Nurfaida; Lantang, Nortje D.J. (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2024)
This study is classroom action research which purpose to improve student learning outcomes through a Problem Based Learning (PBL) model and a Culturally Responsive Teaching (CRT) approach through daily life problems by considering cultural background in order to motivate students to be actively involved in learning. The subjects in this research were 31 class VIII B-Mawar students. To collect data in this  study, it was done through test results and observations. The stages of research carried out are planning, implementing, observing and reflecting. This study was carried out in stages with two cycles, namely cycle one and cycle two. The research results show that using a PBL model with a CRT approach can improve student learning outcomes. This is proven by the increase in student learning outcomes from cycle one to cycle two, namely 29%. Student learning activities were declared quite active in cycle one and increased to active in cycle two, namely with a percentage of 20,50%.